2020
DOI: 10.21203/rs.3.rs-59384/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Priming Intermittent Theta Burst Stimulation on Movement-Related and Mirror Visual Feedback-Induced Sensorimotor Desynchronization

Abstract: Background: The potential benefits of priming intermittent theta burst stimulation (iTBS) with continuous theta burst stimulation (cTBS) have not been examined in regard to sensorimotor oscillatory activities recorded in electroencephalography (EEG). Objective: The objective of this study was to investigate the modulatory effect of priming iTBS (cTBS followed by iTBS) delivered to the motor cortex on movement-related and mirror visual feedback (MVF)-induced sensorimotor event-related desynchronization (ERD), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This finding differed from a study with healthy adults, in which 4-session priming iTBS increased the movement-related ERD. 24 Our study found that ERD triggered by different tasks might represent different sensorimotor processing, and movement-related ERD might be expressed in different manners in stroke patients, compared with their healthy counterparts. Neuroimaging studies have demonstrated that patients with chronic stroke showed an overactivation of bilateral motor-related areas during paretic hand movements, relative to their healthy counterparts.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This finding differed from a study with healthy adults, in which 4-session priming iTBS increased the movement-related ERD. 24 Our study found that ERD triggered by different tasks might represent different sensorimotor processing, and movement-related ERD might be expressed in different manners in stroke patients, compared with their healthy counterparts. Neuroimaging studies have demonstrated that patients with chronic stroke showed an overactivation of bilateral motor-related areas during paretic hand movements, relative to their healthy counterparts.…”
Section: Discussionmentioning
confidence: 57%
“…Participant in Group 3 received cTBS at 20% RMT followed by iTBS at 20% RMT (ie, sham stimulation). Sham stimulation was delivered using the same coil with 20% RMT, 24 which significantly eliminated the TMS-induced electrical fields in the cortex (Figure 1C, the simulation of electrical field was performed using SimNIBS 25 ). We measured the RMT of the contralesional M1 to determine the intensity of stimulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we did not have a real sham condition in this experiment. Nonetheless, our study included a low intensity (50% RMT) condition, comparable to a number of TMS studies that have adopted the strategy of lowering stimulation intensity as a sham condition (49,71,72). Second, due to the inherent limitation of the fNIRS equipment used, such as the height profile of our fNIRS probes we were unable to measure the hemodynamic response to iTBS during and immediately after the stimulation.…”
Section: Discussionmentioning
confidence: 99%